GAYA KEPEMIMPINAN INSTRUKSIONAL KEPALA SEKOLAH PADA ERA PANDEMI COVID 19 - Innova Riana Yanti Sinambela; Sri Ganda Cibro; M. Joharis Lubis (Jurnal Inovasi Penelitian, 2022)
This study aims to determine the principal's instructional leadership style during the Covid-19 pandemic. This research was conducted with a qualitative systematic review approach. The meta-synthesis method with a meta-aggregation approach was chosen to answer questions by summarizing various research results related to school leadership in the era of the covid-19 pandemic. The principal's instructional approach is implied by offering the right services to educators in conducting learning, creating new learning ideas that are adapted to the COVID-19 pandemic era, and offering support and a positive impression for all school members.